A integralidade no cotidiano da estratégia saúde da família em municípios do Vale do Jequitinhonha - Minas Gerais - Selma Maria da Fonseca Viegas (2010)
Multiple case studies of qualitative approach based on the Quotidian Comprehensive Sociology. The objective was to understand the construction of integrality practices in health in the everyday work of Family Health teams and of managers of cities from Vale do Jequitinhonha-MG: Datas, Diarnantina, Gouveia. These sceneries are changing, when it comes to health assistance, especially in primary attention, due to the implementation of Family Health Strategy (FHS) between the years 1995 - 1998. The FHS brought complex challenges to be overcome in order to reinforce the attention model that values actions of health promotion, disease prevention and integral attention to people. The subjects of this study were professionals of Family Health, support teams and managers, coming to a total of 48 people from seven teams located in six Basic Health Units. To collect data, direct observation was done with 43 subjects, and interviews based on semi-structured scrip were done with 35 subjects. It is important to highlight that five subjects were only interviewed and two of them were approached during conversations with a non-structured script for data collection related to the history and to the social-political context of the city. The data was submitted to Thematic Content Analysis proposed by Bardin (2008) and organized in six categories: 1. The look of a researcher brings the interpretation of the observed data; 2. Talking about integrality corresponds to the comprehension of the social actors when it comes to integrality; 3. Pathways and possibilities: both sides of integral practices in the FHS discuss the actions involved in the everyday of professionals, pointing the possibilities of integrality in the everyday of teams; 4. The pillars of integrality: the communion of ideology and the barriers of quotidien translates data convergence in the multiple cases and shows the fundaments to integrality in health: the bond; the professional formation and the profile, the hierarchy process of services and the implication of reference and of counter-reference in the everyday of the System; 5. Implications of integrality in health management highlights the importance and the complexity of a municipal health strategy formulation to construct integrality; 6. An agenda to integrality presents proposals to contribute to those who seek to reinforce integrality practices. The notion expressed by the informants is that integrality is not limited to policies formulation, or to articulation of technique or of certain ways to intervene in health. This notion is also based on the rescue of individual and collective as the center of health care in the FHS, and the family is the action space. Data show that there are already directions and initiatives that seek to construct a differentiated action in everyday practice. This work is intended to contribute to the construction of knowledge about the theme of integrality to the Family Health Strategy. It also aspires to contribute to the daily practice of professionalism of Family Health teams and municipal managers, presenting improvement strategies and analyzing the factors that influence the effectiveness of health integrality, which is the base of possible interventions seeking the improvement of attending the users of FHS in the studied sceneries.